EXPLORING THE INDONESIAN ECONOMIC LANDSCAPE AND STRUCTURAL CHANGE - Muhammad Firdaus; Budi Kurniawan; Sri Mulatsih (Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
In assessing the economic impact of a sector or a group of sectors on a single or multiregional economy, input-output analysis has been proven to be a popular method.This paper explores the degree of structural change of the Indonesian economy using the input-output frame work. It examines how linkages among economic sectors have evolved from 1971-2008 and identifies which economic sectors exhibited the highest inter-sectoral linkages. The study finds that manufacturing consistently becomes the key sector in the Indonesian economy. Indonesian cannot afford to leapfrog the industrialization stage and largely depend on a service-oriented economy when the potential for growth still lies primarily in manufacturing. The graphical presentation of inter-industry relationship through the “Multiplier Product Matrix” (MPM) and its associated “economic landscape” provides a visualization of the Indonesian economic landscape for selected years and how it has changed over time.Keywords: economic landscape, structural change, input output model, key sector